Understanding the illness representations of young people with anxiety and depression: a qualitative study - Bear, HA; Krause, KR; Edbrooke-Childs, J; Wolpert, M (Wiley, 2021)
Background: Many young people with anxiety or depression drop out of treatment early, and/or leave treatment without showing measurably improved symptom levels. To enhance treatment engagement and effectiveness, it is critical to better understand how young people’s perceptions of the symptoms, causes, consequences, treatability, and course of their anxiety and depression influence engagement.